Gancidin W, a potential low-toxicity antimalarial agent isolated from an endophytic Streptomyces SUK10 - Mohamad Zin, Noraziah; Baba, Mohd Shukri; Zainal-Abidin, Abu Hassan; Latip, Jalifah; Mazlan, Noor Wini; Edrada-Ebel, RuAngelie (Dove Medical Press Ltd., 2017)
Endophytic Streptomyces strains are potential sources for novel bioactive molecules. In this study, the diketopiperazine gancidin W (GW) was isolated sfrom the endophytic actinobacterial genus Streptomyces, SUK10, obtained from the bark of Shorea ovalis tree, and it was tested in vivo against Plasmodium berghei PZZ1/100. GW exhibited an inhibition rate of nearly 80% at 6.25 and 3.125 ï¿½g kg-1 body weight on day four using the 4-day suppression test method on male ICR strain mice. Comparing GW at both concentrations with quinine hydrochloride and normal saline as positive and negative controls, respectively, 50% of the mice treated with 3.125 ï¿½g kg-1 body weight managed to survive for more than 11 months after infection, which almost reached the life span of normal mice. Biochemical tests of selected enzymes and proteins in blood samples of mice treated with GW were also within normal levels; in addition, no abnormalities or injuries were found on internal vital organs. These findings indicated that this isolated bioactive compound from Streptomyces SUK10 exhibits very low toxicity and is a good candidate for potential use as an antimalarial agent in an animal model. ï¿½ 2017 Zin et al.